Understanding transporter specificity and the discrete appearance of channel-like gating domains in transporters - Diallinas, George (Frontiers in Pharmacology, 2014)
Transporters are ubiquitous proteins mediating the translocation of solutes across cell membranes, a biological process involved in nutrition, signaling, neurotransmission, cell communication and drug uptake or efflux. Similarly to enzymes, most transporters have a single substrate binding-site and thus their activity follows Michaelis-Menten kinetics. Substrate binding elicits a series of structural changes, which produce a transporter conformer open towards the side opposite to the one from where the substrate was originally bound. This mechanism, involving alternate outward- and inward-facing transporter conformers, has gained significant support from structural, genetic, biochemical and biophysical approaches. Most transporters are specific for a given substrate or a group of substrates with similar chemical structure, but substrate specificity and/or affinity can vary dramatically, even among members of a transporter family that show high overall amino acid sequence and structural similarity. The current view is that transporter substrate affinity or specificity is determined by a small number of interactions a given solute can make within a specific binding site. However, genetic, biochemical and in silico modeling studies with the purine transporter UapA of the filamentous ascomycete Aspergillus nidulans have challenged this dogma. This review highlights results leading to a novel concept, stating that substrate specificity, but also transport kinetics and transporter turnover, are determined by subtle intramolecular interactions between a major substrate binding site and independent outward- or cytoplasmically-facing gating domains, analogous to those present in channels. This concept is supported by recent structural evidence from several, phylogenetically and functionally distinct transporter families. The significance of this concept is discussed in relationship to the role and potential exploitation of transporters in drug action.